2018
DOI: 10.12659/msm.910191
|View full text |Cite
|
Sign up to set email alerts
|

SC79, the AKT Activator Protects Cerebral Ischemia in a Rat Model of Ischemia/Reperfusion Injury

Abstract: BackgroundActivation of AKT pathway attenuates brain damage and neuronal apoptosis during cerebral ischemia/reperfusion (I/R) injury. SC79 is a novel, selective and highly-efficient Akt activator. This study aimed to investigate the neuroprotective effect of SC79 against cerebral I/R injury in a rat model, and to explore the possible underlying mechanisms.Material/MethodsMale Sprague-Dawley rats received cerebral ischemia for 1 hour, followed by brain reperfusion for 0.5–24 hours. The cerebral I/R injury anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The analysis of Cyt c phosphorylation state post-treatment resulted in complete dephosphorylation of Cyt c in the presence of wortmannin, suggesting a potential role for Akt in mediating this pathway. Interestingly, several studies have shown that Akt activator SC79 is an effective treatment for cerebral ischemia/reperfusion injury in animal models [ 54 , 55 , 56 ]. We and others have shown that activated, phosphorylated Akt translocates to the mitochondrial IMS where Cyt c resides [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of Cyt c phosphorylation state post-treatment resulted in complete dephosphorylation of Cyt c in the presence of wortmannin, suggesting a potential role for Akt in mediating this pathway. Interestingly, several studies have shown that Akt activator SC79 is an effective treatment for cerebral ischemia/reperfusion injury in animal models [ 54 , 55 , 56 ]. We and others have shown that activated, phosphorylated Akt translocates to the mitochondrial IMS where Cyt c resides [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue sections were stained histochemically using hematoxylin and eosin (H&E) (Beyotime Biotech., Shanghai, China) and were examined by light microscopy, as previously described [17]. Photomicrographs of the tissue sections were taken using a light microscope (Olympus, Tokyo, Japan) at a magnification of ×400.…”
Section: Methodsmentioning
confidence: 99%
“…Activated Akt influences a number of factors involved in apoptosis, either by transcription regulation or direct phosphorylation, yielding favorable effects against ischemia-induced apoptosis. Thus, chemicals capable of inducing Akt expression/activity may be used in the treatment of I/R injury (2,3235).…”
Section: Introductionmentioning
confidence: 99%